2009
DOI: 10.1007/s11307-009-0203-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of 18F-FDG PET/CT in Patients with Malignant Pleural Mesothelioma

Abstract: Detection of extrathoracic metastases on FDG-PET/CT and nonepithelioid histopathology are poor prognostic indicators in patients with MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…For instance, the presence of metastatic disease on PET-CT has, not surprisingly, been shown to be associated with poorer survival (15). Furthermore, one study showed that patients who had an SUVmax greater than 10 had decreased survival (16).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the presence of metastatic disease on PET-CT has, not surprisingly, been shown to be associated with poorer survival (15). Furthermore, one study showed that patients who had an SUVmax greater than 10 had decreased survival (16).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review [37] of FDG-PET/CT performed in patients with biopsy-proven MPM, mean SUV max of primary MPM in patients with metastatic disease was significantly higher than in patients with MPM without metastatic disease (pG0.05). Longer survival was noted in patients without metastases (pG0.05).…”
Section: Prognosis Defined By Fdg Uptake Of Tumormentioning
confidence: 96%
“…The first was reported by Tan et al and involved the evaluation of 44 patients using PET/CT after multimodality therapy for MPM (Tan, 2010). The other study was reported by Lee and was a retrospective study involving 46 patients who were evaluated using PET/CT for staging or re-staging after therapy for MPM (Lee et al, 2009). Both studies concluded that detecting extrathoracic metastases using FDG-PET/CT indicates poor prognosis in patients with MPM.…”
Section: Pet For Restaging and Survivalmentioning
confidence: 99%